Improvement of personnel policy in the state civil service in the Оffice of the State Duma of the Federal Assembly of the Russian Federation - I. A. Dimaeva; D. Yu. Znamenskiy (Вестник университета)
The problems caused by the need to improve the quality of the personnel of the state civil service are analysed. The article is prepared on the basis of a study in the form of a sociological survey conducted in the Apparatus of the State Duma of the Federal Assembly of the Russian Federation with the aim of the most detailed and objective study of the effectiveness of personnel policy in the office of legislative bodies of state power, in particular in the Apparatus of the State Duma, and subsequent development of recommendations for improving personnel policy. The main emphasis is made on the development of personnel policy based on modern mechanisms for the formation of personnel. A number of recommendations and measures are formulated to perfect the motivation and improve the professional level of state civil servants of the State Duma Apparatus.